Theoretic and Methodological Bases of Human Capital Development - MAZHITOVA, Saule; SATKALIYEVA, Tamara; TASPENOVA, Gaukhar; ABELDANOVA, Aigerim; MALGARAEVA, Zhanat (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article analyzes conditions where the formation and development of domestic human capital takes place at. It is established that despite the great variety of elements of the environment where the human capital is formed and develops, the policy of income and expenses of the population, accessibility and quality of education, protection of health of the population carry the most important value. The problems that are obstacles in the formation of human capital significantly impacting the needs of the new economy have been found.